The Cost of Private Debt Over the Credit Cycle - Tereanu, Eugen; Aykut, Dilek; Francis, Johanna (Washington, D.C. : International Monetary Fund, 2010)
We identify global and regional fluctuations in international private debt flows to emerging and developing countries using data on cross border loans and international bond issuance over 1993 -2009. We estimate the effects of individual borrower characteristics as well as macroeconomic conditions on the cost of foreign borrowing and test whether these effects differ across phases of the lending cycle. We find that public and financial institutions benefit from lower spreads compared to private and nonfinancial firms and that lenders may differentiate the risk associated with the borrower's industrial sector between good and bad times. The loan (bond) rating has an equally robust spread reduction effect across credit cycle phases. The results also suggest that international reserve holdings and investment ratios have a significant effect on reducing credit spreads for loans, while higher reserve holdings and longer maturities matter more for bond spreads.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet